ESL Literacy Development and Storybook Reading: Implementation and Evaluation of A "Smart" Partnership Project - Bava Harji, Madhubala (2002)
The project was undertaken in the light of growing concern of stakeholders and Ministry of education at the decline of English performance and proficiency among Malaysian students as well as poor attitudes towards reading in general. The evaluation aims to assess the children's development of isolated an integrated aspects of ESL development in this study.